2023
DOI: 10.3390/microorganisms11030618
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models for Studying Congenital Transmission of Hepatitis E Virus

Abstract: One of the most intriguing issues in the hepatitis E virus (HEV) field is the significant increase in mortality rates of the mother and fetus when infection occurs in the second and third trimesters of gestation. A virus that is normally self-limiting and has a mortality rate of less than one percent in otherwise healthy individuals steeply rises by up to 30% in these pregnant populations. Answering this pivotal question has not been a simple task. HEV, in general, has been a difficult pathogen to understand i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 140 publications
0
6
0
Order By: Relevance
“…Few cases of HEV-gt3 infections reported in pregnant women have not been associated with severe disease or deaths [ 93 , 94 , 95 ]. As of today, there are no animal models that recapitulate all the clinical manifestations of vertical transmission of HEV as seen in humans [ 88 , 96 , 97 , 98 , 99 , 100 ].…”
Section: Seminal Studies From Kashmirmentioning
confidence: 99%
“…Few cases of HEV-gt3 infections reported in pregnant women have not been associated with severe disease or deaths [ 93 , 94 , 95 ]. As of today, there are no animal models that recapitulate all the clinical manifestations of vertical transmission of HEV as seen in humans [ 88 , 96 , 97 , 98 , 99 , 100 ].…”
Section: Seminal Studies From Kashmirmentioning
confidence: 99%
“…However, recent data from China has shown that HEV-gt4 can cause placental injury and obstetric events, but maternal disease is usually asymptomatic and not severe [20]. Despite many HEV studies attempting to elucidate pregnancy mortality, a definitive mechanism contributing to pregnancy pathogenesis has been complex and debated [21,22]. Open reading frame 4 (ORF4) protein expressed in HEV-gt1 during endoplasmic reticulum stress has been suggested as important for enhancing viral replication and could potentially contribute to severe pregnancy morbidity [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…However, the pathogenesis of HEV infection during pregnancy is not fully understood. In this issue, Yadav and Kenney discussed the animal models used to study the congenital transmission of HEV to understand the pathogenesis of HEV during pregnancy [27]. The authors first described the immunological and hormonal changes during pregnancy [27].…”
mentioning
confidence: 99%
“…In this issue, Yadav and Kenney discussed the animal models used to study the congenital transmission of HEV to understand the pathogenesis of HEV during pregnancy [27]. The authors first described the immunological and hormonal changes during pregnancy [27]. There is no ideal animal model that can study HEV pathogenesis during pregnancy from all aspects, though non-human primates could be suitable for studying HEV genotypes 1-4 [27].…”
mentioning
confidence: 99%
See 1 more Smart Citation